Impacts of coal particle size and secondary air ratio on NO and N2O emissions in a 10 kW circulating fluidized bed: Experimental and numerical simulation - Yingchuan Zhou; Yanjun Zuo; Haiyang Li; Zhaoxin Wan; Rui Jin; Xiaojia Wang; Yufeng Duan (Fuel, 2026)

N2O and NO formation influenced by metal elements during coal pyrolysis and char combustion - Yanjun Zuo; Zhaoxin Wan; Haiyang Li; Ping Liu; Xiaoshuo Liu; Yingchuan Zhou; Zhi Han; Yufeng Duan (Fuel, 2026)

Fish Diversity and Spatial Patterns in the Upper Yangtze River National Nature Reserve for Rare and Endemic Fish Based on Environmental DNA (eDNA) Technology - Xiaohan Dong; Jiaxin Huang; Zongqiang Qi; Ziwei Wang; Qing Zuo; Yanjun Shen (Fishes, 2025)
The Upper Yangtze River National Nature Reserve for Rare and Endemic Fish is a critical sanctuary facing increasing pressure from hydropower development. To assess its current ecological state, we employed environmental DNA (eDNA) metabarcoding on 48 water samples collected from 16 transects in August 2024. Our analysis identified 93 fish species from 3 orders, 13 families, and 67 genera, of which 89 were consistent with historical records. The Cyprinidae family was dominant. The fish community was predominantly characterized by slow-flowing, benthic, omnivorous, and migratory taxa that lay adhesive eggs, with key life-history traits including a sexual maturity age of 1–4 years and a length at first maturity under 20 cm. Spatially, species richness was highest in the Chishui River (64 species), followed by the Minjiang River (61 species). While alpha diversity was largely consistent across most rivers (except the Minjiang), beta diversity analysis revealed significant compositional differences among basins (PERMANOVA, R2 = 0.2747, p = 0.001). Notably, the Chishui River supported not only the highest richness but also a distinct community structure. In summary, this study provides a systematic current status assessment of the reserve’s fish resources, revealing significant spatial heterogeneity, Our findings underscore the potential impacts of dam construction and offer a scientific basis for informing effective conservation strategies.

N2O and NO formation and inhibition influenced by calcium (Ca) during coal char combustion - Zhi Han; Ping Liu; Yanjun Zuo; Yingchuan Zhou; Xiaoshuo Liu; Xunlei Ding; Jianming Xue; Yufeng Duan (Fuel, 2025)

Sustainable and effective degradation of high concentration of aniline by acetylguanidine activated persulfate - Runlai Ji; Wenming Chen; Yanjun Zuo; Yi Xin; Jingjing Zhang; Haibo Wang; Lingce Kong; Yufeng Wu (Environmental Geochemistry and Health, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

High-entropy perovskite embedded in carbon-based catalyst toward peroxymonosulfate activation to degrade Rhodamine B: Performance and mechanism insights - Zihao Chen; Xingqi Huang; Yanjun Zuo; Haibo Wang; Wenming Chen; Lingce Kong; Xiaoyan Lin (Water Research, 2025)

Dynamic Rockfall Hazard Assessment at Railway Tunnel Portal: Application of G1-FCE Method and 3D Numerical Simulation - Shengwei Zhang; Jiaxing Dong; Yanjun Shen; Qingjun Zuo; Junli Wan (Journal of Earth Science, 2025)

Mechanism of rainfall-induced loess landslides revealed by multi-source data - HongYu Liu; YanJun Li; MingZhou Bai; Xu Gao; Ling Yang; ZiLun Zhang; MingHui Zuo; Qain Liu (Natural Hazards, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

Microwave-assisted hydrothermal synthesis of highly dispersed cerium–zirconium solid solution on Ti3C2Tx nanosheets as an efficient decontamination towards sulfur mustard simulants - Xingqi Huang; Haibo Wang; Lingce Kong; Zihao Chen; Jingjing Zhang; Yanjun Zuo; Wenming Chen (Journal of Hazardous Materials, 2024)

Unraveling roles of the intermediate settler in a microaerobic hydrolysis sludge in situ reduction process - Zhen Zhou; Yiyue Sun; Li Fu; Yi Zuo; Yanjun Shao; Lihua Wang; Chuanting Zhou; Ying An (Bioresource Technology, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)